Ethnobotanical Study on the Use of Mangroves as a Food Source in Pesawaran Regency, Lampung Province - Melviani; Duryat; Melya Riniarti (Journal of Sylva Indonesiana, 2025)
The current global food crisis requires heightened attention from various countries, including Indonesia. In addressing this issue, mangrove plants present significant potential to be developed as alternative sources of functional food. This study aimed to document ethnobotanical practices related to the use of mangrove plants as food sources in Pesawaran Regency, Lampung Province. The research was conducted from March to June 2024 in Sidodadi and Gebang Villages, Teluk Pandan District, Pesawaran Regency. A snowball sampling technique was employed to collect comprehensive data regarding the use of mangrove plants as food ingredients. The information gathered included the plant species utilized, specific plant parts used, processing methods, food products derived, and their perceived benefits. Data were obtained through interviews, observations, and documentation, and were analyzed using a descriptive-analytical approach to elucidate usage patterns and processing methods of mangroves as functional food sources. The findings revealed that coastal communities in Pesawaran Regency utilize two types of mangrove plants for food: Legundi (Vitex trifolia) and Bakau (Rhizophora mucronata). These species are processed into various food products, including kitchen spices, flour, syrup, and coffe, which serve not only as nutritional items but are also believed to possess medicinal and health-promoting properties